DEVELOPMENT OF TEACHING MATERIALS FOR HANDLING HAZARDOUS AND NON HAZARDOUS WASTE BASED ON SETS - Millaturosita Zeni Hidayana; Rusmini Rusmini (JCER (Journal of Chemistry Education Research), 2021)
Abstract. The purpose of this study is to obtain the feasibility of teaching materials that handle hazardous and non-hazardous waste based on Science, Environment, Technology, and Society (SETS). The research design used refers to the 4-D development model (four-D Models) recommended by Thiagarajan which consists of four stages, namely define, design, develop, and disseminate, which is limited to the development stage. The samples in this study were 34 students of class X 2 SMK Negeri 5 Surabaya. The results showed that the validity of teaching materials obtained a percentage of 83,27% with a very valid category, observation of students 97.62% was very practical, the test of student learning outcomes increased with the acquisition of N-Gain of 0.7 in the category high, as many as 100% of students achieve mastery learning and the questionnaire responses of students as much as 90.59% are very practical. This shows that SETS-based teaching materials on hazardous and non-hazardous waste handling materials for vocational high school students are proper to be used in the learning process.